Development Of Processed Catfish Through A Canvas Business Model Approach - Muh. Aras; Ayu Wulandary; Iranita Haryono (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
Catfish processing in Sidrap Regency, especially in Makkoring Village, requires optimization for business development. The aim of this research is to analyze the canvas model business and provide business improvements in the Pokdakan Massiddie Fish Cultivation Group. The analytical method used in the research is descriptive qualitative, while the data analysis technique used is BMC (Business Model Canvas). The data used includes primary and secondary data. The research results show that the Pokdakan Massiddie Fish Cultivation Group's business model needs to be improved in the elements of customer relationships, channels, revenue streams, key resources, key activities, key partners and cost structure. For customer segments and value proposition elements, there is no need for improvement, it just needs to be maintained.